Pengaruh Perencanaan Produksi terhadap Ketepatan Waktu Penyajian dan Kepuasan Konsumen pada Restoran D’Cost - Ahmad Zuhrofi; Izzati Rizal (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study aims to examine the effect of Production Planning on Service Timeliness and Customer Satisfaction at D’Cost Restaurant. A quantitative approach was employed using a survey method involving 400 customers, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a second-order reflective–reflective model. The measurement model evaluation indicates that all constructs meet the required validity and reliability criteria. The structural model results reveal that Production Planning has a positive and significant effect on Service Timeliness. Furthermore, Service Timeliness significantly influences Customer Satisfaction, while Production Planning also exerts a significant direct effect on Customer Satisfaction. The mediation analysis confirms that Service Timeliness serves as a partial mediator in the relationship between Production Planning and Customer Satisfaction. These findings highlight that effective production planning enhances customer satisfaction primarily through timely and consistent service delivery. This study provides practical implications for restaurant management by emphasizing the importance of integrated operational planning to improve service quality and customer satisfaction.